TOU-AR:Touchable Interface for Interactive Interaction in Augmented Reality Environment - Ahmad Hoirul Basori; Hani Moaiteq Abdullah AlJahdali (Universitas Sriwijaya, 2017)
Touchable interface is one of the future interfaces that can be implemented at any medium such as water, table or even sand. The word multi touch refers to the ability to distinguish between two or more fingers touching a touch-sensing surface, such as a touch screen or a touch pad. This interface is provided tracking the area by using depth camera and projected the interface into the medium. This interface is widely used in augmented reality environment. User will project the particular interface into real world medium and user hand will be tracked simultaneously when touching the area. User can interact in more freely ways and as natural as human did in their daily life